Broad-specificity time-resolved fluorescent immunochromatographic strip for simultaneous detection of various organophosphorus pesticides based on indirect probe strategy. Issue 10 (23rd February 2022) - Dong, Haowei; Xu, Deyan; Wang, Guanjie; Meng, Xiaoya; Sun, Xia; Yang, Qingqing; Guo, Yemin; Zhu, Yelong
Abstract : An indirect probe strategy could effectively realize signal amplification, and save the amount and protect the activity of Abs. Abstract : The massive use of organophosphorus pesticides (OPs) poses a great threat to food safety, human health and environmental protection. As there are many kinds of pesticides, their detection is facing a severe challenge. The simultaneous detection of multiple organophosphorus pesticides in one test is a problem to be solved at present. In this paper, a time-resolved fluorescent immunochromatographic (TRFIA) strip is prepared by using broad-specificity antibodies (Abs) of OPs as the recognition element. Abs were connected to europium oxide latex microspheres using sheep anti-mouse antibodies (SaMIgG) to form an indirect probe. This strategy could effectively realize signal amplification, and could save the amount and protect the activity of Abs. After the detection, the color change of the test line (T-line) was observed to make qualitative judgment under UV-light (365 nm). Then, the images of the positive sample were analyzed by using ImageJ to complete the quantitative detection. Under optimal construction and operating conditions, the limit of detection of the strip could reach 0.53 ng g −1 . And the TRFIA strip performed well in the additive test of vegetable samples. It is inexpensive to prepare, convenient to carry, and easy to operate. More importantly, it improves the detection efficiency and meets the needs of rapid field testing of a large number of samples.